Spinal pain revealing brucellar spondylodiscitis: a case report - Lamia Oulkadi; Bouchra Amine; Imane El binoune; Samira Rostom; Rachid Bahiri (SpringerOpen, 2021)
Abstract Background Brucellosis is an anthropozoonosis. It is an endemic disease in the Mediterranean basin. The clinical presentation is polymorphic. The osteoarticular form is the most frequent of the focal forms affecting mainly the spine. In our endemic context, the diagnosis can lead to confusion with tuberculosis. Case presentation We report a case of brucellar spondylodiscitis treated initially as tubercular spondylodiscitis with a good initial evolution. Then, the diagnosis was rectified towards a Brucella origin, after a clinical and biological relapse. Diagnostic confirmation was based on the isolation of Brucella spp in the disco-vertebral CT-guided biopsy and the positive Brucella serology. Then, the patient was put on three antibacterial treatments with doxycycline, rifampicin, plus streptomycin over a period of 6 months with a good evolution. Conclusion Brucellar spondylodiscitis is still common in the Maghreb. It is generally insidious and leads to a delay in diagnosis. The clinician must always mention it when faced with spondylodiscitis in an endemic country and ask for brucella serology.